Numerical and Experimental Study on the Opening Angle of the Double-Stage Flap Valves in Pumping Stations - Xi, Wang; Lu, Weigang; Wang, Chuan; Fu, Guocong (Frontiers in Energy Research, 2022)
The double-stage flap valves are widely used in new pumping stations. The different opening angles of the double-stage flap valves greatly influence on the outflow. To gain insight into this phenomenon, four commonly used operating conditions with opening angles were selected to perform three-dimensional simulation calculations and physical model studies on the flow pattern of the water behind the valves at different flow rates. The flow pattern of the water flow is analyzed by three indicators: the streamline of the water flow, the uniformity of the flow velocity, and the head loss in the culvert. The result shows that the coefficient of resistance loss along the way of the outlet culvert has a negative correlation with the opening angle. The larger the opening angle of the flap valve, the less the head loss of the water flow in the outlet culvert, and the flow pattern of the water flow in the culvert gradually becomes better.